Komunikasi dan Pola Asuh Anak dalam Membangun Keharmonisan pada Keluarga Tenaga Kerja Indonesia (Kasus pada Tenaga Kerja Indonesia di Sojomerto, Kendal) - Dhesanto Surya Gani; Sri Budi Lestari (Interaksi Online, 2018)
Alongside with the demands of needs in each household, the fulfillment of these demands is achieved with varied methods, one of which is by working abroad as Tenaga Kerja Indonesia (TKI/Indonesian Workers). Individuals departing as Indonesian workers carry a consequence, that is a shifting in communication process within their family. This study aims to describe the Pattern of Communication and Nurturing in Indonesian Labor Family in building harmony within their family by implementing qualitative approach and case study method with pattern matching data analysis technique. The subjects of this study involve three families that work abroad as Indonesian Workers. Theory applied in this study is the Family Communication Patterns Theory and Relational Dialectics Theory. The results of this study show that the consensual and protective patterns that have been predicted before are found. Consensual Patterns are found in couple 1 and 2 each of who are characterized by high-conversation orientation and high-compliance orientation. High-conversation orientation is accomplished through the participation of the entire family members in intense, honest, and open communication activity. Meanwhile, high-compliance orientation is characterized by parents that are dominant in making decisions for the family members although the parents still listen to every opinion from each family member. Protective Patterns are found in couple 3 who is characterized with low-conversation orientation that is achieved through low communication rate between the children and parents. Protective parents are characterized by decision making that is in the hands of the parents. Despite the different communication and nurturing patterns, the three families left by one family member working abroad manage to have a harmonious life as they have enough time to live a good religious life, build affection within the family, respect fellow family members, minimalize conflicts, and construct a strong bond between family members.